1998
DOI: 10.1021/ja980838a
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Stereochemistry of Chiral Molecules from ab Initio Theoretical and Experimental Molecular Optical Rotations

Abstract: Optical rotations of a diverse set of chiral molecules have been calculated ab initio. In a majority of the molecules considered, the signs of the calculated optical rotations are in agreement with those of the corresponding experimental observations, and the magnitudes are in reasonable agreement. It is thus suggested that the ab initio optical rotations provide a convenient alternative approach to determine the absolute stereochemistry of chiral molecules. A group of molecules has also been identified where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 50 publications
1
65
2
1
Order By: Relevance
“…Other factors that lead to a disagreement between the calculated and the experimental results have already been extensively discussed in the literature. 8,17,18 In particular for the molecules without a chromophor such as a bond, the optical rotations are dominated by Rydberg excitations which in turn are subject to sizeable solvent effects. Apparently, the present density functional approach offers both a reasonable accuracy and error compensation in order to allow the prediction of optical rotations within the aforementioned range of errors without the need for modeling solvent effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors that lead to a disagreement between the calculated and the experimental results have already been extensively discussed in the literature. 8,17,18 In particular for the molecules without a chromophor such as a bond, the optical rotations are dominated by Rydberg excitations which in turn are subject to sizeable solvent effects. Apparently, the present density functional approach offers both a reasonable accuracy and error compensation in order to allow the prediction of optical rotations within the aforementioned range of errors without the need for modeling solvent effects.…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory statements can be found in the literature whether it is mandatory 17 or not 8,18 to enforce the gauge-independence of chiroptical properties, which seems to be partially motivated by the availability or nonavailability of a respective code implementation. Very recently, it has been shown that, provided use is made of high quality basis sets including diffuse functions, physically meaningful results can be obtained for optical rotations without explicitly enforcing the gauge invariance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stephens and coworkers 7,9,10,[12][13][14][15] have assessed the accuracy of the B3LYP exchange-correlation functional 16,17 in optical rotation calculations at the molecular equilibrium geometry. For a test set of 30 chiral molecules with absolute values of experimental sodium D-line specific optical rotations ranging from $10-12008 (dm g/cm 3 ) 21 a mean absolute deviation of 208 (dm g/cm 3 ) 21 was found. 13 For smallangle rotations [absolute value <1008 (dm g/cm 3 ) 21 ], the wrong sign was predicted for about 12% of 65 molecules at the sodium D-line.…”
Section: Introductionmentioning
confidence: 95%
“…The optical rotatory power is a much more difficult observable, since the whole spectrum contributes. Only very recently have ab initio calculations been reported for this property [16,17].…”
Section: Introductionmentioning
confidence: 99%